Opening Materials - Ralf Haekel; Caroline Lusin (Review of Irish Studies in Europe)
Up until the 1990s, the concept of Irish literature appeared to be fairly unanimous. Literary texts considered to be typically Irish were predominantly concerned with the Irish socio‐political context, critically reflecting the history and conditions of Irish identity formation: the struggle for independence and its aftermath, the family, the church and the nation. The social and political changes from the 1990s and early 2000s onwards, initiated by the Celtic Tiger and the decline of the Catholic Church in the wake of the abuse scandal, which fundamentally transformed Irish culture and politics, can also be witnessed in contemporary Irish literature. In the twenty-first century, the 'national obsessiveness, which in Ireland has predominantly found expression in realist and naturalist modes of writing' (5), as Eoghan Smith puts it, has gradually made way for a new and decidedly more open literary scene. Not only has Irish literature started to embrace new topics, moving away from its preoccupation with its own history and 'the Irish argument' (Tóibín); it has also turned to new genres and modes of writing, and it is now more inclusive of authors from social groups and ethnicities formerly ignored by the literary marketplace. This themed issue sets out to explore the scope and variety of the Irish literary scene in the twenty-first century by focusing on new forms of authorship, new subjects, new genres as well as new approaches to familiar issues, showcasing new voices and new directions shaping the Irish literary scene.